Early Warning for Currency Crises: What Is the Role of Financial Openness?. Issue 4 (20th March 2014) - Frost, Jon; Saiki, Ayako
Abstract The paper explores whether financial openness—capital account openness and gross capital inflows—makes countries vulnerable to currency crises. A quarterly dataset on 46 advanced and emerging market economies (AEs and EMEs) during 1975Q1–2011Q4 is used, with the period after Q2 2007 used for out‐of‐sample testing. The key findings are: (1) capital account openness is associated with lower probability of currency crises, but less so for EMEs; (2) surges in gross capital flows are associated with increased risk of currency crises; and (3) the model performs well out‐of‐sample, confirming that early warning models are helpful in judging relative vulnerability.